Study protocol for the development of a digital menstrual cycle diary for routine mental health and gynecological care: A human-centered design approach - Michèle Schmitter; Astrid Cantineau; Marije aan het Rot; Annemiek Lely; Tom Verhage; Michelle N. Servaas; Harriëtte Riese (PLoS ONE, 2026)
Background Premenstrual disorders, including premenstrual syndrome, premenstrual dysphoric disorder, and premenstrual exacerbation of psychiatric disorders affect a significant portion of reproductive-age females. Accurate diagnosis and tailored treatment are often constrained by the limitations of traditional paper-based symptom diaries. These diaries lack flexibility for personalized symptom tracking and fail to capture treatment-relevant factors such as lifestyle and social events. A digital, adaptable symptom diary is therefore needed. In this paper, we present the protocol for the CycleWise study. This study is a multi-method study aimed at developing a digital menstrual cycle diary within PETRA (PErsonalized Treatment by Real-time Assessment), an ESM-based tool previously designed to support treatment in routine mental health care. Methods and analysis Following a human-centered design approach and the Centre for eHealth and Wellbeing Research roadmap, patients and clinicians will be involved throughout all phases to ensure the tool meets their needs. In the contextual inquiry phase, we will identify stakeholders and analyze current practices. The value specification phase will focus on assessing stakeholder needs through two focus groups and translating them into functional requirements. A user experience designer will then develop a prototype in the design phase, refining it iteratively based on stakeholder feedback. Implementation strategies will be formulated in the operationalization phase. Finally, uptake, impact and working mechanisms will be evaluated through qualitative interviews and quantitative measures.